Implementation of Corporate Criminal Accountability in Indonesian National Economic Crime - Deny Prabowo; Yasmirah Mandasari Saragih; Muhammad Faiz Hadi; Sagita Ifani Emri; Kaaisar Romolus Deo Sianipar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Corporations as legal entities have become an integral part of the national economic system. However, behind its contribution to economic growth, not a few corporations are involved in economic crimes such as corruption, tax evasion, money laundering, to monopoly and cartel practices. These corporate crimes have a broad and systemic impact, not only harming the state from a financial perspective, but also damaging a healthy economic order and creating social injustice. In the context of Indonesian criminal law, the implementation of accountability for corporations as perpetrators of criminal acts still faces various challenges, both in terms of regulations, technical law enforcement, and understanding of law enforcement officials. This research aims to evaluate the extent to which the implementation of criminal liability against corporations in cases of national economic crimes as well as identify relevant obstacles and solutions. The method used is a normative juridical approach by examining various laws and regulations, jurisprudence case studies, and related scientific literature. The results show that although the recognition of corporations as subjects of criminal law has been contained in several sectoral laws, its implementation is still partial and has not touched the root of the problem, especially in proving structural corporate guilt. Therefore, there is a need for regulatory reform, strengthening the capacity of law enforcement institutions, and integrating a multidisciplinary approach in dealing with corporate crime. By strengthening criminal accountability towards corporations, it is hoped that the Indonesian criminal law system will be able to provide a deterrent effect while maintaining national economic integrity.